PENGEMBANGAN MEDIA PEMBELAJARAN KOMIK ELEKTRONIK MELAN (MENGENAL IKLAN) PADA SUB MATERI IKLAN - Nurmala, Nurmala; Elfitra, Legi; Wahyusari, Ahada; Andheska, Harry; Shanty, Isnaini Leo; Ariance Loren, Fabio Testy; Suhardi, Suhardi; Irawan, Dody (Universitas Tanjungpura, 2024)
The aim of this research is to develop a learning media for Electronic Comics MELAN (Getting to Know Advertising), which will be used by Class VIII students of SMP Negeri 1 Tanjungpinang in the 2023/2024 academic year. Type of RD research, using the 4D model. Electronic comics that can be accessed via the web and applications are digital products developed in this research. This media has been evaluated by two experts, namely a material expert and a media expert. The small group trial consisted of six students and the large group trial consisted of thirty eight students. Qualitative and quantitative descriptive methods were used to analyze the data in this research. The results showed that 91.25% of media had